Surgical treatment of pathologic fractures in patients with metastatic tumors - Zore, Zvonimir (Array, 2009)
Abstract: The study presents results in treatment of pathologic fractures of long bones of all patients who underwent surgery in the last 10 years in our hospital. The study cohort comprised 133 consecutive patients divided in two groups who underwent surgery of long bone fractures caused by metastatic tumor or trauma. We used resection, open reduction and plating with bone cement application for pathologic fracture and some cases of femoral shaft fractures were stabilized with intramedullary nailing. Proximal femoral fractures were treated with hip arthroplasty or dynamic hip screw. There were 2 amputations performed: one case of pathologic fracture of tibia and one case of humeral fracture. The present study compares results between two group of patients. We noted: age, gender, fracture site, choice of the surgical procedure, hospital stay, need for analgesia after surgery, postoperative complications, and reached level of physical activity after surgery. The mean survival rate was 8.1 months. Seventeen patients experienced postoperative complications. We also found statistically significant improvement in functional scores (MSTS and TESS) in surgically treated patients with pathologic fractures. There are many different techniques of surgical treatment of pathologic fractures caused by skeletal metastases including arthroplasty or a combination of internal fixation combined with polymethyl methacrylate (PMMA) that provides immediate fixation and stability. The present study showed that surgical treatment of pathologic fractures caused by skeletal metastases in vast majority of cases provides bone healing after pathologic fracture, with signifficant improvement of physical activity and rehabilitation in the investigated group